2022
DOI: 10.3390/su14159784
|View full text |Cite
|
Sign up to set email alerts
|

Does ISO 14001 and Green Servitization Provide a Push Factor for Sustainable Performance? A Study of Manufacturing Firms

Abstract: This study contributes to the development of a green servitization framework to achieve manufacturing firms’ sustainable performance using ISO 14001 as a driving factor in their operational management system. Manufacturing firms are becoming concerned due to the associated problem of physical flow of materials and energy through the ecosystem, which can hinder resource sustainability for future generations as a result of the enormous waste and emission of carbon produced by their operations. This is possible d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 115 publications
0
4
0
Order By: Relevance
“…While most participants within this study noted their organisations are using ISO14001 to manage both environment and sustainability objectives within their operations, some are still separating-out issues such as waste management and energy-use into an EMS while another department has responsibility for sustainability matters. It is suggested that this results in a doubling-up on costs, as environment and sustainability are inextricably linked and rationalising these areas could increase benefits (Boiral and Henri, 2012;Oyelakin and Johl, 2022). It is interesting to note the concern expressed in relation to the not achieving objectives and this brings into question whether all objectives should be to be ticked off the to do list in one or two years or being aspirational;…”
Section: Discussionmentioning
confidence: 99%
“…While most participants within this study noted their organisations are using ISO14001 to manage both environment and sustainability objectives within their operations, some are still separating-out issues such as waste management and energy-use into an EMS while another department has responsibility for sustainability matters. It is suggested that this results in a doubling-up on costs, as environment and sustainability are inextricably linked and rationalising these areas could increase benefits (Boiral and Henri, 2012;Oyelakin and Johl, 2022). It is interesting to note the concern expressed in relation to the not achieving objectives and this brings into question whether all objectives should be to be ticked off the to do list in one or two years or being aspirational;…”
Section: Discussionmentioning
confidence: 99%
“…Current research has emphasized the role of digital servitization in ecosystems [73], and we enrich the theoretical framework of digital ecosystems by introducing the concept of digital infrastructure. The current research on the improvement of enterprise sustainable performance has been discussed from the perspective of digital technology and services [26,27,38]. We advance the research object of this issue to the strategic transformation of business models brought about by digital technology and service upgrading.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental performance is achieved not only by establishing a sense of corporate social responsibility, but also by representing the management capability of a firm [70,71]. Firms who have attained ISO14001 can take advantage of their scientific model to improve the efficiency of management systems [26], including the rigor and effectiveness of practices, regulatory compliance, greener supply chain, and documentation control [70,71], so that their management level can be significantly improved and all aspects of control and responsiveness can be optimized [70]. Establishing a macroenvironmental management system is also a process of improving firms' ability to work in synergy with partners [11,32].…”
Section: Digital Infrastructure and Sustainabilitymentioning
confidence: 99%
See 2 more Smart Citations